Field rhetoric ethnography, ecology, and engagement in the places of persuasion - Rai, Candice 1976-; Druschke, Caroline Gottschalk (Rhetoric, culture, and social critique, 2018)
"Places of Persuasion explores innovative scholarship emerging at the intersection of rhetoric and field-based studies, or ethnography. Field methods allow researchers to capture rhetoric-in-action and to observe the dynamic circumstances that shape persuasion in ordinary life. The recent proliferation of rhetorically oriented fieldwork warrants a collection that gathers, describes, and theorizes this burgeoning, interdisciplinary (and even transdisciplinary) body...and method...of scholarship. Places of Persuasion documents and supports this ethnographic turn in rhetorical studies through a sustained examination of the diverse trends, methods, tools, theories, practices, and possibilities for engaging in rhetorical field research. The book offers an introduction to these inquiries, and serves as both a practical resource and theoretical foundation for scholars, teachers, and students hoping to work at the intersection of rhetoric and field studies. The collection will also provide a useful resource for interdisciplinary qualitative researchers interested in doing research from a rhetorical or discursive perspective in diverse disciplines, such as English, composition, communication, natural resources, geography, sociology, urban planning, and anthropology"...